Chrząszcze saproksyliczne (Coleoptera) obszaru ochrony ścisłej Bukowa Góra w Roztoczańskim Parku Narodowym - Papis, Magdalena; Mokrzycki, Tomasz (Leśne Prace Badawcze, 2015)
The aims of this study were to demonstrate the role of forests in the Roztoczański National Park as a refuge for rare and endangered saproxylic Coleoptera as well as recognition of entomological fauna related to dead wood. The study was conducted in the strictly protected are of Bukowa Góra from 20th April to 30th September 2012 and focused on the wood of beech and fir. We inventoried saproxylic beetles by means of nine ‘Netocia’ traps, which resulted in a total of 135 recorded species, of which 52 had not been reported in the park before. Twenty-one rare and endangered species were found. The high number of new species in the Roztoczański National Park indicates a high biodiversity value of the area. Our studies therefore show that the strictly protected area of Bukowa Góra is a biodiversity hot spot of saproxylic Coleoptera.